A coating steel plate with high ductility and production method thereof

By adopting a specific component system and a multi-stage rolling process in the steel plate, a complex microstructure is formed, which solves the problem of insufficient impact resistance and corrosion resistance of steel plates in the marine environment in the prior art, and achieves a steel plate with high elongation, good weldability and high collision resistance, which is suitable for offshore floating structures.

CN116200656BActive Publication Date: 2025-03-25ANGANG STEEL CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202211610435.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-14
Publication Date
2025-03-25
Estimated Expiration
2042-12-14

AI Technical Summary

Technical Problem

The prior art is difficult to provide steel plates with high elongation, good weldability and high collision resistance in marine environments with high humidity, high salt and high irradiation. It is also difficult to meet the impact resistance needs of offshore floating structures.

Method used

A new steel ingredient system is adopted, including C, Si, Mn, Mg, Ca, V, N, Cu, Ni, Mo, W, Re, Cr, REM, Sn, Ti, P and S. Through a multi-stage rolling and cooling controlled process, a structure of 20-25% low-carbon bainite and 70-80% bulk ferrite is formed. Combined with the precipitation of nanophase, the mechanical properties and corrosion resistance of the steel plate are improved.

Benefits of technology

The steel plate has achieved high elongation (≥32%), uniform elongation (≥20%), high tensile strength and good welding performance, and the corrosion resistance of the coating system has been improved by 80-160%, which can effectively deal with the collision risk in the marine environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003999387870000091
    Figure BDA0003999387870000091
  • Figure BDA0003999387870000101
    Figure BDA0003999387870000101
  • Figure BDA0003999387870000102
    Figure BDA0003999387870000102
Patent Text Reader

Abstract

The invention discloses a steel plate for coating with high ductility and a production method thereof. The steel comprises C0.02-0.04%, Si0.5-0.7%, Mn0.2-0.4%, Mg0.005-0.01%, Ca0.008-0.015%, V: 0.03-0.05%, N0.007-0.01%, Cu0.7-1%, Ni0.8-1.2%, Mo0.05-0.1%, W0.05-0.1%, Re0.02-0.03%, Cr0.6-1%, REM0.03-0.05%, Sn0.15-0.2%, Ti0.001-0.005%, P0.01-0.015%, and S≤0.005wt%. The method includes the following steps: the billet temperature is ≤100°C, multi-stage heating is adopted, the first stage final rolling temperature is 1000-1150°C, the second stage final rolling temperature is 915-940°C, the cooling rate between the two rollings is 0.5-2°C / s, the steel plate is relaxed to 500-550°C and then cooled, and the cooling rate is 2-4°C / s; the holding temperature is 300-350°C. The steel grade of the present invention takes into account strength, toughness, weldability, and collision resistance, and has a high coating coupled corrosion resistance, which solves the collision risk problem faced by marine equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal material preparation, and particularly relates to a coating steel plate with high ductility and a production method thereof. Background Art

[0002] International offshore wind power projects are showing a trend of development from nearshore to offshore. The demand for the construction of floating wind power will continue to increase in the future. The service environment of floating wind power is more severe than that of traditional marine structural steel. The floating wind power foundation structure is subjected to alternating stresses such as wind and waves at sea for a long time, and is at risk of being hit by the hull and marine floating objects. This puts forward higher requirements on the impact resistance and pitting corrosion resistance of structural steel. Similar scenarios also include various floating and fixed marine platforms and ocean-going ships in the deep sea. The stress corrosion problems caused by these offshore equipment and welding nodes cannot be ignored.

[0003] my country's South China Sea is the sea area with the richest offshore wind resources and is the direction of my country's medium- and long-term development of offshore wind power resources. However, this sea area is also one of the sea areas with the worst marine environment in the world. According to the ISO9223 classification standard, in this high-humidity, high-salt, and high-irradiation area, the corrosion level of materials can reach the highest level C5. Compared with other regions, surface ships, ground buildings, equipment and facilities, and offshore floating platforms serving in this environment will suffer from severe corrosion prematurely even if corrosion protection measures are taken. According to statistics, the failure rate of equipment and facilities serving in the South China Sea is three times that of other sea areas and about 10 times that of the mainland. It can be said that a material that adapts to the service requirements of the South China Sea environment can basically meet the material needs of all sea areas in my country, and how to balance cost and performance is an important proposition.

[0004] The invention patent with application number CN201710075154.0 and name “A high corrosion-resistant low-alloy steel suitable for high-temperature coastal environment” has better corrosion resistance than Q235 carbon steel and other weathering steels. However, due to the use of a high Ni system and alloying with elements such as Cu and Mo, the problem is that the cost is relatively high, and due to the high alloying and carbon equivalent, there are problems with welding performance. In addition, this system steel has stress corrosion problems, and as the strength increases, the hydrogen-induced cracking problem of the steel structure becomes prominent, there are major safety hazards, and the elongation is low, only about 15%. Similar cases include the invention patent with application number CN201611097512.X and name “A high-strength weathering steel resistant to high-humidity and heat marine atmosphere environment”, and the invention patent with application number CN201611102046.X and name “High-strength weathering steel resistant to high-humidity and heat marine atmosphere environment and preparation method”.

[0005] The invention patent with application number CN202010044231.8 and the name of "A weathering steel resistant to high temperature, high humidity and high salt fog marine atmospheric environment" adopts a low Ni and high Cr composition formula, with a low elongation of only about 12%, which cannot meet the technical requirements of marine anti-collision. The above studies are all aimed at improving the corrosion resistance of materials in the South China Sea environment, and there are high costs, poor weldability, and low elongation, especially the uniform elongation that is crucial for anti-collision performance. There is no solution to the anti-collision performance of offshore floating structures represented by offshore wind power in the complex waters of the South China Sea.

[0006] For the anti-collision steel with high ductility, the invention patent with application number 201910999129.0 and name “Method for manufacturing EH32 grade marine engineering steel and steel plate with high ductility” adopts a three-stage rolling process to control the ratio of ferrite and pearlite, and the process is complicated. Application number 201810320311.4 and name “A high ductility EH40 grade ship plate steel and its preparation method” also adopts a multi-stage rolling and multi-stage water cooling process, which is complex and difficult to implement industrially; in addition, the above patents do not have the ability to resist atmospheric corrosion in marine environments. In addition, for some coastal construction environments with extremely harsh environments, not only steel is required to have good corrosion resistance, but also steel and coating systems are required to play a coupled anti-corrosion role and improve long-term service safety to cope with the failure and corrosion hazards caused by local damage and local aging of the coating. There is no special steel for use in a coating system that is resistant to harsh marine environments. Summary of the invention

[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a coated steel plate with high ductility and a production method thereof. Through a new component system design and corresponding production process, the developed steel type takes into account strength and toughness, weldability, good collision resistance, and high coating coupled corrosion resistance, effectively solving the collision risk problem faced by marine equipment in marine environment.

[0008] In order to solve the above problems, the technical solution adopted by the present invention is as follows: a steel plate for coating with high ductility, wherein the steel composition comprises C: 0.02-0.04wt%, Si: 0.5-0.7wt%, Mn: 0.2-0.4wt%, Mg: 0.005-0.01wt%, Ca: 0.008-0.015wt%, V: 0.03-0.05wt%, N: 0.007-0.01wt%, Cu: 0.7-1wt% %, Ni: 0.8-1.2wt%, Mo: 0.05-0.1wt%, W: 0.05-0.1wt%, Re: 0.02-0.03wt%, Cr: 0.6-1wt%, REM: 0.03-0.05wt%, Sn: 0.15-0.2wt%, Ti: 0.001-0.005wt%, P: 0.01-0.015wt%, S: ≤0.005wt%, the balance is Fe and other inevitable impurities.

[0009] Furthermore, the average grain size of the steel plate is 30-50μm, containing 20-25% low-carbon bainite + 70-80% blocky ferrite structure, and the percentage is the area percentage; it contains spherical V (C, N), WC, Mo2C, Fe3C nanophases with an average size of 15-25nm dispersed and precipitated, and the average spacing of these precipitated phases is 1.2-2μm; it contains Cu nanophases with an average size of 43-65nm, and the average spacing of the phases is 2-2.5μm.

[0010] Furthermore, the dispersed and precipitated V (C, N), WC, Mo2C, and Fe3C nanophases have a size of 10-40 nm, and the Cu nanophase has a size of 30-80 nm.

[0011] Furthermore, the average grain size of the surface layer -1 / 8 of the thickness of the steel plate is 20-30 μm.

[0012] Furthermore, the yield strength of the steel is 360-400 MPa, the yield strength ratio is ≤0.74, the impact energy at -60°C is not less than 220 J, the elongation is ≥32%, and the uniform elongation is ≥20%.

[0013] Furthermore, the tensile strength of the welded joint is controlled at 510-550MPa under 35KJ line energy conditions, and the impact energy at -60°C is not less than 130J.

[0014] The present invention provides a method for producing a steel plate for coating with high ductility, including smelting, continuous casting, billet heating, controlled rolling and controlled cooling, and off-line processing, the specific contents of which are as follows:

[0015] Billet heating: The billet is cold loaded into the furnace at a temperature of ≤100°C, and multi-stage heating is adopted, wherein the total time at 650-1000°C is controlled within 0.2-0.3min / mm, the total time at 1230-1240°C is controlled within 0.1min / mm, and the total time at 1200-1220°C is controlled within 0.2-0.4min / mm;

[0016] Controlled rolling and controlled cooling: In the first stage, the final rolling temperature is controlled at 1000-1150℃, and the pass reduction is controlled at 12-20%. In the second stage, the final rolling temperature is controlled at 915-940℃, and the pass reduction is controlled at 15-25%. Cooling is used as a transition between the two rolling passes, and the cooling rate is 0.5-2℃ / s. After rolling, the steel plate is relaxed to 500-550℃ and then cooled down at a cooling rate of 2-4℃ / s.

[0017] Off-line treatment: After the steel plate is off the line, the second stage precipitation phase and internal stress are regulated by insulation treatment, and the insulation regulation temperature is 300-350℃.

[0018] Furthermore, the steel is smelted in a converter, the Ti element in the molten iron is controlled below 0.005%, and Si and Mn are used for deoxidation.

[0019] Furthermore, the steel billet is made by converter smelting + continuous casting, and cooling begins when the surface temperature of the steel billet is 830-870°C, and the cooling rate is controlled at 4-11°C / s, followed by low-temperature heating treatment at a heating temperature of 200-360°C.

[0020] The coated steel sheet produced according to the above scheme has the following beneficial effects:

[0021] 1. The corrosion resistance of the steel plate is greatly improved by adding composite trace elements and their synergistic effect. Using a simulated South China Sea seawater splash zone immersion test, the corrosion resistance of the steel plate coating system is improved by 80-160% compared with 3.5Ni system steel.

[0022] 2. It has good comprehensive mechanical properties, structural safety and weldability, with a yield strength of 360-400Mpa, a yield strength ratio of ≤0.74, and an impact energy of not less than 220J at -60℃; under 35KJ line energy conditions, the tensile strength of the welded joint can be controlled at 510-550Mpa, and the impact energy of not less than 130J at -60℃.

[0023] 3. Elongation ≥ 32%, uniform elongation ≥ 20%. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other examples improved or modified by ordinary technicians in this field belong to the scope of protection of the present invention. It should be understood that the embodiments of the present invention are only used to illustrate the technical effects of the present invention, rather than to limit the scope of protection of the present invention.

[0025] The present invention aims at the more complex environment of high temperature, unstable oxygen, low pH value and high Cl- faced by steel materials under the coating system. By adding low-noble metals, adding composite trace elements and the synergistic effect, the pH value of the anode area is reduced, the system potential is improved, the local pH value is reduced, and the coupled passivation ability of the steel-coating system is improved. The developed steel plate has good comprehensive performance of mechanical-corrosion resistance matching, coupled corrosion resistance of the coating, and high anti-collision performance. Using a simulated immersion test in the splash zone of South China Sea seawater, the corrosion resistance of the coating system of the steel plate is improved by 80-160% compared with 3Ni system steel, which effectively solves the anti-collision risk problem faced by deep-sea coating equipment in marine environment.

[0026] The steel composition of the present invention will be described in detail below. Unless otherwise specified, the content of each element is expressed in % by weight.

[0027] A steel plate for coating with high ductility, wherein the steel composition comprises, by weight percentage, C: 0.02-0.04wt%, Si: 0.5-0.7wt%, Mn: 0.2-0.4wt%, Mg: 0.005-0.01wt%, Ca: 0.008-0.015wt%, V: 0.03-0.05wt%, N: 0.007-0.01wt%, Cu: 0.7-1wt%, Ni: 0.8-1.2wt% , Mo: 0.05-0.1wt%, W: 0.05-0.1wt%, Re: 0.02-0.03wt%, Cr: 0.6-1wt%, REM: 0.03-0.05wt%, Sn: 0.15-0.2wt%, Ti: 0.001-0.005wt%, P: 0.01-0.015wt%, S: ≤0.005wt%, Ti: ≤0.005, the balance is Fe and other inevitable impurities.

[0028] C: 0.02-0.04wt%

[0029] The C element is the main phase transformation controlling element for forming a corrosion-resistant structure with 20-25% low-carbon bainite + 70-80% fine ferrite as the matrix, and is an important element for ensuring the strength of the steel grade. Appropriate C promotes the formation of important tiny cathode phases V (C, N), WC, Mo2C, and Fe3C in the present invention, and controls the precipitation of large carbides of Cr. These phases help to improve the corrosion resistance of the steel. However, under the component system of the present invention, more C is not good for the corrosion resistance and weldability of the steel, so the C content is 0.02-0.04wt%.

[0030] Si: 0.5-0.7wt%

[0031] The Si element plays a certain role in strengthening and is one of the important deoxidizers of the present invention. It can promote the surface enrichment of Sn and form surface oxides with Cu, Sn, and Cr, effectively improving the corrosion resistance. Appropriate Si can increase the ferrite content and help to improve the potential of the coating system and control the local pH value. Therefore, the Si content is controlled at 0.5-0.7wt%.

[0032] Mn: 0.2-0.4wt%

[0033] The Mn element plays a certain role in strengthening and is one of the important deoxidizers of the present invention. Too much Mn will reduce the corrosion resistance of the steel and affect the solid solution effect of the corrosion-resistant elements in the steel. In addition, Mn is an austenite stabilizing element. Too high Mn is not conducive to the formation of a stable ferrite phase region. Therefore, the Mn content is controlled at 0.2-0.4wt%.

[0034] Ca: 0.008-0.015wt%, Mg: 0.005-0.01wt%

[0035] The Ca and Mg elements are mainly used to reduce the cathode reaction area and the pH value under the coating, which plays a passivation role in protecting Cr; in addition, trace amounts of Ca and Mg dissolved in Fe can make Ni, Cu, Cr, Sn and other corrosion-resistant elements relatively enriched after the surface Fe dissolves in the early stage of corrosion, improve corrosion resistance, and reduce the toughness reduction problem caused by the addition of high Sn and other elements. The above elements will also form a coupling effect with Zn in the primer in a weakly acidic environment to improve the corrosion resistance of the steel-coating system. Based on the above design, the content of Ca and Mg elements is controlled at 0.008-0.015wt% and 0.005-0.01wt%, respectively.

[0036] V: 0.03-0.05wt%

[0037] The V element plays an important role in the toughness and corrosion resistance of steel mainly in the form of precipitation strengthening, and is also an important ferrite stabilizing element. The role of V in the present invention is mainly to form V (C, N) with appropriate proportions of C and N. Since the steel material is a multiphase structure formed by multi-element alloying, the control of the cathode ratio in the micro-region is very important. The refined, dispersed, uniform and distributed cathode design is very important for the control of the corrosion resistance of the complex structural system of the steel material. Based on this, the present invention adopts a trace amount of 0.03-0.05wt% of V to give full play to its excellent precipitation effect. The electrochemical impedance spectrum shows that after full precipitation, the surface inductive arc of the steel grade is greatly weakened, indicating that the pitting phenomenon is effectively suppressed. It mainly plays the role of controlling the cathode phase. Under the configuration of V, C, N and Cr elements adopted in the present invention, it will promote the formation of V (C, N) with an average size of 15-25nm dispersed precipitation in the steel matrix, with an average spacing of 10-30μm, mainly in a spherical shape, which can further prevent the expansion of fatigue cracks. Based on the above design, the content of V is 0.03-0.05wt%.

[0038] N: 0.007-0.01wt%

[0039] The N element mainly promotes the precipitation of fine particles of V (C, N) and Fe3C. In addition, the solid-dissolved N helps to improve the corrosion resistance of the steel and is beneficial to control the ratio of bainite and ferrite. The N in the present invention is controlled at 0.007-0.01wt%.

[0040] Cu: 0.7-1wt%

[0041] Cu is an important corrosion resistance and toughening agent of the present invention. On the one hand, in the early stage of corrosion, after the surface is initially corroded, an enrichment layer and an oxide layer are formed. In addition, a nano phase with an average size of 43-65nm is formed inside the steel plate, and the average spacing between the phases is 2-2.5μm. After the surface rust layer is destroyed, a large number of fine cathode phases are further formed to form a unique cathode size and distribution control system with V (C, N), Fe3C, VN, WC, and Mo2C, which controls the corrosion rate and helps to improve weldability. Appropriate Cu can promote the formation of high ductility ferrite, so the Cu of the present invention is controlled at 0.7-1wt%.

[0042] Ni: 0.8-1.2wt%

[0043] The main function of Ni element is to balance the toughness of weathering steel. In terms of corrosion resistance, it promotes the positive movement of the self-corrosion potential on the steel surface. The present invention adopts a low Mn component design, so that Ni can more effectively promote the formation of Fe3O4 oxides, and Ni in the rust layer 2+ It can more effectively occupy the interstitial position of Fe3O4, forming a stable and dense intermetallic compound of Fe and Ni, preventing Cl -Diffusion into the matrix reduces acidification and increases the pH value of the electrolyte in the rust layer. In addition, too high Ni is not conducive to the formation of high ductility ferrite structure, so Ni is controlled at 0.8-1.2wt%.

[0044] Mo: 0.05-0.1wt%

[0045] Mo element can make the rust layer dense, and when combined with Si, Cu, etc., the oxide film formed is effective against initial corrosion. In addition, along with the anodic reaction of steel, MoO4 2- Dissolved, MoO4 on the rust layer 2- distribution, producing ion selection, resisting the corrosion promoting factor Cl - In addition, the addition of Mo helps to improve the low and high temperature stability of the V and Cu dispersion phases, while precipitating 15-25nm Mo2C, improving its corrosion resistance and slip control ability. Too high is not good for plasticity, so it is controlled at 0.05-0.1wt%.

[0046] W: 0.05-0.1wt%

[0047] W element accompanies the anode reaction of steel, WO4 2- Dissolved, WO4 on the rust layer 2- distribution, producing ion selection, resisting the corrosion promoting factor Cl - In addition, the addition of W helps to improve the low and high temperature stability of the V and Cu dispersed phases, balance the phase ratio, and precipitate 15-25nm WC to improve the comprehensive performance of the steel. Too high W will deteriorate the toughness and be detrimental to the coupling performance of the coating, so it is controlled at 0.05-0.1wt%.

[0048] Re: 0.02-0.03wt%

[0049] The Re element is evenly distributed in the dendrite trunk and between dendrites during the solidification process. It is an important solid solution strengthening element. Its corrosion potential is about 0.3V, which can shift the corrosion potential positively, effectively increase the corrosion potential of the matrix, reduce the corrosion current of the system, and improve the corrosion resistance of steel. In addition, an appropriate amount of Re combined with Ni and Cu can effectively promote anode passivation and improve cathode efficiency. Since the anode current in the passivation zone is several orders of magnitude smaller than the current of activation and dissolution, it is very effective to use cathodic elements to improve the corrosion resistance of the alloy. The addition of Re helps to improve the low-temperature and high-temperature stability of the dispersed phases of V and Cu, and improve the bonding between steel and coating. In addition, the compound addition of Re, V, and Ni can effectively control the toughness control problem caused by the addition of elements such as Sn, so it is controlled at 0.02-0.03wt%.

[0050] Cr: 0.6-1wt%

[0051] Cr element plays a role in compacting the rust layer, and on the other hand, it forms a passivating oxide, which, together with other oxides and dense α-FeOOH, resists Cl - Intrusion; In addition, in the composition design of the multi-component system of the present invention, solid solution elements such as Cr are fully dissolved in the matrix, which reduces the solid solubility of V and improves its precipitation behavior, indirectly controlling the thermodynamic and kinetic changes of V (C, N), and after the compounding of Cr, V and other elements forms a stable rust layer, the inductive impedance effect tends to completely disappear, indicating that the material's fatigue resistance and pitting resistance have reached the best match. However, too much Cr is not conducive to the control of pH under the coating. According to environmental requirements, the Cr of the present invention is controlled at 0.6-1wt%.

[0052] REM: 0.03-0.05wt%

[0053] On the one hand, REM rare earth elements can change the size of cathode phases such as V (C, N), increase their dispersion, increase their potential, and reduce their cathode effect. Because the content reaches 0.03-0.05wt%, it is fully dissolved in the matrix, which plays a role in increasing the matrix potential and directly produces corrosion resistance. The RE absorbed by grain boundaries, subgrain boundaries, precipitate mismatches and other positions plays a role in balancing the segregation of elements such as Cr and Cu, reducing intergranular and interphase corrosion caused by segregation.

[0054] Sn: 0.15-0.2wt%

[0055] On the one hand, Sn element can reduce the energy level of steel and weaken the electrochemical activity of steel in the form of single substance solid solution. In addition, it helps to form oxides such as SnO and deposit on the corrosion front, promote the formation of α-FeOOH, and compact the oxide layer together with α-FeOOH. When dissolved with Fe, ionic Sn can react with Cl - Combined with the above, the local pH value is increased, the corrosion process is accelerated, and the local pH value is increased, especially the pH under the coating, which plays a role in controlling the acceleration of the corrosion process. Therefore, according to environmental requirements, the Sn content of the present invention is controlled at 0.15-0.2wt%.

[0056] Ti: 0.001-0.005wt%

[0057] The Ti element helps to control the initial grain size, but too much will consume the N element, affecting the strength and corrosion resistance of the steel. Therefore, the Ti content of the present invention is controlled within 0.001-0.005 wt%.

[0058] P: 0.01-0.015wt%

[0059] The P element is mainly used to reduce the degree of anode polarization, promote the uniform dissolution of steel and accelerate the oxidation rate of iron, promote the formation of non-static protective film, and cooperate with Re, Cu, etc. to resist Cl- Considering that too much P reduces the weldability of the coated steel to a certain extent, the P in the present invention is controlled at 0.01-0.015wt%.

[0060] S: ≤0.005wt%

[0061] S: The sulfide formed by the element accelerates corrosion and reduces the toughness of the steel plate, so it needs to be strictly controlled to ≤ 0.005wt%.

[0062] In addition to the above-mentioned steel components, the balance of the present invention may be Fe and inevitable impurities. Inevitable impurities are impurities that are not artificially mixed in the general steel manufacturing process. They cannot be completely excluded, and the meaning can be easily understood by those skilled in the art of general steel manufacturing. In addition, the present invention does not completely exclude the addition of other components in addition to the above-mentioned steel components.

[0063] The microstructure of the present invention will be described in further detail below.

[0064] The invention discloses a steel plate for coating with high ductility, wherein the average grain size is 30-50 μm (the average grain size of the surface layer of the steel plate - 1 / 8 of the thickness is 20-30 μm), the steel plate contains 20-25% low-carbon bainite + 70-80% blocky ferrite as a corrosion-resistant structure as a matrix, wherein the percentage is an area percentage; the steel plate contains dispersed precipitated spherical V (C, N), WC, Mo2C, Fe3C nanophases, wherein the size of the precipitated phases is 10-40 nm, the average size is 15-25 nm, and the average spacing is 1.2-2 μm; the steel plate contains dispersed precipitated Cu nanophases, wherein the size is 30-80 nm, the average size is 43-65 nm, and the average spacing is 2-2.5 μm.

[0065] The production process of the present invention is described in further detail below.

[0066] The present invention provides a method for producing a steel plate for coating with high ductility, including smelting, continuous casting, billet heating, controlled rolling and controlled cooling, and off-line processing, which is specifically as follows:

[0067] Smelting: The steel is smelted in a converter, and Si and Mn are used for deoxidation. The use of Al is strictly controlled because the addition of Al will consume the N element and have a harmful effect on the surface quality of the steel billet. Similarly, the introduction of the Ti element in the molten iron should also be strictly controlled (Ti≤0.005%), which affects the precipitation effect of V and Cu and avoids the formation of Ti, Al and other carbonitrides, which are not conducive to corrosion resistance and mechanical properties.

[0068] Continuous casting: The steel billet is made by converter smelting + continuous casting. In order to control the initial surface grain size of the continuous casting billet and the solid distribution of corrosion-resistant elements, rapid cooling is used for pretreatment when the billet is discharged. The surface temperature is controlled at 830-870℃ and the cooling rate is controlled at 4-11℃ / s. After that, it is not suitable for hot loading and low-temperature heating treatment is required. The heating temperature is 200-360℃ to control the surface quality and thermal stress distribution of the steel billet.

[0069] Billet heating: The temperature of the cold billet in the furnace is controlled at ≤100℃, and multi-stage heating is adopted. The total time of 650-1000℃ is controlled within 0.2-0.3min / mm, the total time of 1230-1240℃ is controlled within 0.1min / mm, and the temperature of the soaking section is 1200-1220℃, and the total time is controlled within 0.2-0.4min / mm. The purpose is to control the initial distribution of alloy elements and trace elements before hot working. Since the distribution and composition of grains, especially grain boundaries, have a greater impact on corrosion, it is necessary to reasonably control the initial grain size.

[0070] Controlled rolling and controlled cooling: rolling begins as soon as the steel plate leaves the furnace, and high-temperature controlled rolling is used to control the grain size from the surface to the core of the steel plate. The final rolling temperature in the first stage is controlled at 1000-1150°C, and the pass reduction is controlled at 12-20%. The final rolling temperature in the second stage is controlled at 915-940°C according to the thickness of the rolled steel plate. Cooling is used as a transition between the two rolling passes to prevent mixed crystals from being generated, and to ensure that the single pass reduction of the second stage of rolling is controlled at 15-25%. Cooling is used as a transition between the two rolling passes, and the cooling rate is 0.5-2°C / s. After rolling, the steel plate adopts a relaxation process to control the grain structure and phase ratio, relaxes to 500-550°C, and is quickly cooled off the line at a cooling rate of 2-4°C / s. The average grain size of the steel plate organization is controlled at 30-50μm, among which the average grain size of the steel plate surface -1 / 8 thickness is controlled at 20-30μm. Too fine grain size is not conducive to anti-collision performance. In addition, the importance of this process is not only to control the anti-collision organization, but also to reduce the deviation of precipitation phase control caused by uncontrolled offline thermal history, and to ensure that the components of the main precipitated corrosion-resistant elements in the steel are supercooled to stably control the precipitation process. In this process, a corrosion-resistant organization with 20-25% low-carbon bainite + 70-80% blocky ferrite as the matrix is ​​formed in the steel.

[0071] Off-line treatment: After the steel plates are off the line, they are uniformly stacked and heat-insulated to regulate the second-stage precipitation phase and internal stress. Cooling increases the precipitation dynamics of the fine phase. The 300-350℃ control treatment can be used, which plays a certain role in improving the comprehensive performance matching of the steel plates, especially the surface corrosion resistance.

[0072] After regulation, V (C, N), WC, and Mo2C with a size of 10-40nm (average size 15-25nm) are dispersed and precipitated in the matrix of the steel to form a complex with the Fe3C phase in the steel. The average spacing between these phases is 1.2-2μm. At the same time, there are 30-80nm (average size 43-65nm) of Cu nanophases in the matrix, and the average spacing between the phases is 2-2.5μm.

[0073] According to the above chemical composition and production process, the actual smelting composition of the present invention is shown in Table 1, the actual process parameters of the present invention are shown in Tables 2-5, and the actual properties are shown in Tables 6-10.

[0074] Table 1 Composition of each example, wt%

[0075]

[0076]

[0077] Table 2 Pretreatment of blanks

[0078]

[0079] Table 3 Heating process

[0080]

[0081] Table 4 Rolling process

[0082]

[0083] Table 5 Organization control results

[0084]

[0085]

[0086] Table 6 Steel plate production process and organizational proportion level

[0087]

[0088] Table 7 Mechanical properties of the examples

[0089]

[0090] Table 8 Welding performance of the embodiment (line energy 35KJ, submerged arc welding)

[0091]

[0092] The test steel and the comparison steel were protected by four layers of Zn-rich primer to make the coated steel accelerated corrosion coupons for the steel-coating accelerated corrosion test. The single test method was as follows:

[0093] 1. 42℃, relative humidity 90%, time 5h;

[0094] 2. An accelerated corrosion test simulating the South China Sea conditions was used, 2% NaCl solution: pH value: PH: 6-6.9, immersion temperature 42±2℃, time 1h;

[0095] 3. Exposure temperature 45±2℃, exposure humidity 60%, time 10h;

[0096] The number of times that 10% coating degradation (peeling of notched parts, bubbling, etc.) occurs after corrosion cycles is used as an evaluation of the corrosion resistance of the system. The number of corrosion cycles is 61 to 83, and the relative corrosion resistance is 185% to 252%.

[0097] Table 9 Corrosion resistance of the examples

[0098] Corrosion cycles Relative corrosion resistance Comparative Example (3.5Ni Steel) 33 100% Example 1 64 194% Example 2 62 188% Example 3 61 185% Example 4 69 209% Example 5 65 197% Example 6 71 215% Example 7 64 194% Example 8 68 206% Example 9 72 218% Example 10 83 252%

[0099] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A steel plate for coating with high ductility, characterized in that: The steel plate composition includes C: 0.02-0.04wt%, Si: 0.5-0.7wt%, Mn: 0.2-0.4wt%, Mg: 0.005-0.01 wt%, Ca: 0.008-0.015wt%, V: 0.03-0.05 wt%, N: 0.007-0.01 wt%, Cu: 0.7-1wt%, Ni: 0.8-1.2wt%, Mo: 0.05-0.1 wt%, W: 0.05-0.1 wt%, Re: 0.02-0.03 wt%, Cr: 0.6-1wt%, REM: 0.03-0.05 wt%, Sn: 0.15-0.2wt%, Ti: 0.001-0.005wt%, P: 0.01-0.015 wt%, S: ≤0.005 wt%, the remainder is Fe and other inevitable impurities; The average grain size of the steel plate is 30-50μm, containing 20-25% low-carbon bainite + 70-80% massive ferrite structure, and the percentages are area percentages; it contains spherical V (C, N), WC, Mo2C, Fe3C nanophases with an average size of 15-25nm dispersed precipitation, and the average spacing of these precipitated phases is 1.2-2μm; it contains Cu nanophases with an average size of 43-65nm, and the average spacing of the phases is 2-2.5μm.

2. A steel plate for coating with high ductility according to claim 1, characterized in that: The dispersed precipitated V (C, N), WC, Mo2C, Fe3C nanophase size is 10-40nm, and the Cu nanophase size is 30-80nm.

3. The steel sheet for coating with high ductility according to claim 1, characterized in that: The average grain size of the steel plate surface layer - 1 / 8 thickness is 20-30μm.

4. The steel plate for coating with high ductility according to claim 1, characterized in that: The yield strength of the steel is 360~400Mpa, the yield strength ratio is ≤0.74, the impact energy at -60℃ is not less than 220J, the elongation is ≥32%, and the uniform elongation is ≥20%.

5. The steel sheet for coating with high ductility according to claim 1, characterized in that: Under the condition of 35KJ line energy, the tensile strength of the welded joint is controlled at 510~550MPa, and the impact energy at -60℃ is not less than 130J.

6. A method for producing a steel sheet for coating having high ductility according to any one of claims 1 to 5, characterized in that: It includes smelting, continuous casting, billet heating, controlled rolling and cooling, and off-line processing. The specific contents are as follows: Billet heating: The billet is cold loaded into the furnace at a temperature of ≤100°C, and multi-stage heating is adopted, wherein the total time at 650-1000°C is controlled within 0.2-0.3min / mm, the total time at 1230-1240°C is controlled within 0.1min / mm, and the total time at 1200-1220°C is controlled within 0.2-0.4min / mm; Controlled rolling and controlled cooling: In the first stage, the final rolling temperature is controlled at 1000-1150℃, and the pass reduction is controlled at 12-20%. In the second stage, the final rolling temperature is controlled at 915-940℃, and the pass reduction is controlled at 15-25%. Cooling is used as a transition between the two rolling passes, and the cooling rate is 0.5-2℃ / s. After rolling, the steel plate is relaxed to 500-550℃ and then cooled down at a cooling rate of 2-4℃ / s. 3) Off-line treatment: After the steel plate is off the line, the second stage precipitation phase and internal stress are regulated by insulation treatment, and the insulation control temperature is 300-350℃.

7. The method for producing a steel sheet for coating with high ductility according to claim 6, characterized in that: The steel plate is smelted in a converter, the Ti element in the molten iron is controlled below 0.005%, and Si and Mn are used for deoxidation.

8. The method for producing a steel sheet for coating with high ductility according to claim 6, characterized in that: The steel billet is made by converter smelting + continuous casting. The steel billet starts to cool when the surface temperature is 830-870°C, and the cooling rate is controlled at 4-11°C / s. It is then subjected to low-temperature heating treatment at a heating temperature of 200-360°C.

Citation Information

Patent Citations

  • High-strength high dampness and heat sea atmospheric environment resistant weathering resistant steel and preparing method

    CN106756476A

  • High-damp-heat-resistant marine atmosphere high-strength weathering resistant steel

    CN106756602A

  • High-anticorrosion low alloy steel suitable for high-temperature littoral environment

    CN106929751A

  • A high-ductility EH40 grade ship plate steel and its preparation method

    CN108517462B

  • Manufacturing method of EH32 grade marine engineering steel and steel plate with high ductility

    CN110846554B